Community participation in microfinance scheme as a medium for empowerment in developing nations with special reference to Nigeria - Saidu, Mohammed Bashir; Abu Samah, Asnarulkhadi (Faculty of Economics and Management, Universiti Putra Malaysia, 2012)
For the past two decades, microfinance scheme has become a key instrument for community empowerment in developing countries. In recent years the scheme has attracted international attention thereby assuming a prominent place in community development discourse. This paper discuses the role of microfinance scheme as a tool for community empowerment in Nigeria. The previous literatures revealed that successive Nigerian governments in the past initiated a series of public financed programmes and policies targeted at the poor but unfortunately, all those programmes have failed to deliver. In-line with this therefore, the author reviews the current Nigerian government policy on National Economic Empowerment Development Strategy (NEEDS) where microfinance scheme is identified as one of the key instrument for empowerment which the author perceived as bottom-up approach. The author found out that the reason why those initial programmes failed to deliver was that the subsequent government used top-down approach which leads to little or no empowerment at all. Therefore, this paper proposed a model of microfinance in the Nigeria context. The framework of the model portrays the relationship between empowerment and community participation which shows high level of empowerment at various stages in order to support the argument that bottom-up approach is relatively appropriate for community development.